Eco-guilt and eco-shame in everyday life: an exploratory study of the experiences, triggers, and reactions - Nielsen, Rikke Sigmer; Gamborg, Christian; Lund, Thomas Bøker (Frontiers in Sustainability, 2024)
Guilt and shame are often mentioned in the context of environmental problems. Exploring how such emotions affect individuals and their behavior is crucial to the effective promotion of more pro-environmental behavior and sustainable consumption. The aim of this article is to further the understanding of eco-guilt and eco-shame by studying these emotions among participants with differing levels of environmental concern (EC). Using a phenomenologically inspired approach, we conducted 18 in-depth interviews with Danish citizens. A clear connection between EC and the experienced emotions emerged, including how these emotions were triggered and how participants reacted to them. While individuals with high EC mainly experienced eco-guilt, individuals with low EC mainly experienced eco-shame and individuals with a medium level of EC experienced both emotions. Both eco-guilt and eco-shame can increase pro-environmental behaviors under certain conditions, but their effects are complex, and eco-shame in particular, risks leading to environmentally harmful behaviors. Therefore, harnessing these emotions to promote pro-environmental behavior introduces moral as well as practical considerations. The novelty of this study is that it questions the view that certain environmental emotions are inherently adaptive or maladaptive and underscores the importance of understanding the individual and social dynamics, which can affect how eco-guilt, eco-shame and their pro-environmental effects are experienced.